Pile design and construction practice - Tomlinson, M. J. (Michael John); Woodward, John, 1936- (CRC Press, 2015)
"This international piling handbook is essential for geotechnical engineers and engineering geologists responsible for designing and constructing piled foundations. It explains general principles and practice and details current types of pile, piling equipment and methods. It includes calculations of the resistance of piles to compressive loads, pile groups under compressive loading, piled foundations for resisting uplift and lateral loading and the structural design of piles and pile groups. Marine structures, durability of piled foundations, ground investigations, and pile testing are also covered as are miscellaneous problems such as machinery foundations, underpinning, mining subsidence areas, geothermal piles and unexploded ordnance.This edition has been fully up-dated to apply the latest version of Eurocode 7 and the UK National Annex, and refers to other structural Eurocodes for steel, concrete and timber relevant to pile design. New British Standards covering pile construction and material testing are extensively cross-referenced to provide a comprehensive text compatible with the Eurocodes, and aspects of now withdrawn BSI codes are retained where useful to the designer. Changes to the procurement and management of civil engineering contracts applicable to piling projects are summarised. It is well illustrated and includes numerous examples, re-worked to the codes, many based on actual problems"--